'You can't Google everything': the voluntary sector and the leadership of communities of place. (February 2022) - Rees, James; Sancino, Alessandro; Jacklin-Jarvis, Carol; Pagani, Michela
Responding directly to the themes of the Special Issue, this paper addresses a surprising absence to date of the voluntary sector's important role in the constitution of place leadership. Drawing on an empirical study of locally rooted voluntary sector organisations in a district of the Midlands of England, we aim to untangle the complex relationship between leadership, place and the voluntary sector, building on recent advances in the collective and critical approaches to leadership studies. A thematic analysis of a rich qualitative dataset highlighted three core themes of the voluntary sector contribution to collective place leadership: their ability to draw on and mobilise local knowledge, their positioning in a web of dense local relationships, and the notion that their intrinsic characteristics are a key source of their distinctiveness and value to the local governance network that constitutes the district's place leadership. In addition to contributing to a nuanced understanding of the voluntary sector's place in both the leadership and place leadership studies corpus, our findings shed light on the multiplexity and tensions of leading in the collective, as well as the extent to which the voluntary sector is constrained by wider structures and macro-dynamics.